Closure of large lumbosacral defect using a combined method of bilateral bipedicle flap with lateral releasing incision and Integra® dermal regeneration template - Pauline Yap; Arman Zaharil Mat Saad; Wan Azman Wan Sulaimana; Siti Fatimah Noor Mat Johar; Nurul Syazana Mohamad Shah (Clinical case, 2021)
BACKGROUND: Myelomeningocele is one of the most complex congenital malformations of the central nervous system. It is one of the most common types of spina bifida which involves a failure of neural tube closure. Reconstruction surgery for myelomeningocele had always been challenging for plastic and neurosurgeons. CLINICAL CASE: We report a case of a new-born with lumbosacral myelomeningocele who received treatment in the Hospital Universiti Sains Malaysia. The myelomeningocele was repaired by the neurosurgery team and subsequently, the child was left with huge lumbosacral skin defect. The large defect was successfully covered by using a combined method of bilateral bipedicle flap with lateral releasing incision and remaining lumbosacral and secondary defect resurfaced using Integra® dermal regeneration template (DRT). We used ACTICOAT interfaced negative pressure wound therapy (NPWT) as our main dressing in preparing the wound bed for autologous epidermal graft. The result of our closure technique provides tension free closure. DISCUSSION: We incorporated bilateral bipedicle fasciocutaneous flap technique together with DRT for closure of the lumbosacral defect. The bilateral bipedicle flap with lateral releasing incision served to reduce tension on the skin at bilateral lumbar region. The DRT downsized the lumbosacral defect and NPWT dressing provided an optimal sterile environment in giving time for neodermis generation. The remaining secondary defect were also resurfaced utilizing DRT and autologous skin grafting. CONCLUSIONS: The outcome of surgery demonstrated that the combined use of bilateral bipedicle fasciocutaneous flap with lateral releasing incision and DRT with delayed skin grafting is safe, effective and provide long term stable and supple scar for large, exposed dura defect.